The notion and contents of organized criminality in the sphere of economic activity - Некрасов, В. А. (Problems of legality, 2013)
The article is concerned with the definition of notion and contents of modern infrastructure of criminality in the sphere of economic activity. In this article are considered the principles of building, the elements of modern infrastructure of economic crimes and within this infrastructure act the criminal technologies of this sphere.